Ultra-low friction between polymers and graphene oxide multilayers in nitrogen atmosphere, mediated by stable transfer film formation. (October 2017) - Saravanan, Prabakaran; Selyanchyn, Roman; Tanaka, Hiroyoshi; Fujikawa, Shigenori; Lyth, Stephen Matthew; Sugimura, Joichi
Abstract: The efficiency and lifetime of mechanical devices is significantly decreased by friction and wear, significantly contributing to global energy consumption. We previously showed that multilayer polyethyleneimine/graphene oxide thin films, (PEI/GO)15, on steel display superlubricity against a steel counterface ball. Here, the coefficient of friction (COF) and wear of (PEI/GO)15 with six different counterface polymer balls is investigated in air and in nitrogen, with particular focus on the formation of tribological transfer films. The polymers polyoxymethylene (POM), polyetheretherketone (PEEK), polyethylene (PE), poly(methyl methacrylate) (PMMA), polycarbonate (PC), and polytetrafluoroethylene (PTFE) are utilized. The COF of (PEI/GO)15 vs steel is 0.35 in both air and nitrogen. In air, the COF ranges from 0.06 to 0.17 for all polymers. Significantly, in nitrogen, four polymers (POM, PEEK, PMMA and PC) display ultra-low friction (COF ∼0.02) whilst two do not (PTFE and PE). The wear tracks and transfer films are investigated using e.g. optical microscopy, electron microscopy, and Raman mapping, and the tribological behavior is correlated to the hydrophilicity and relative hardness of the polymer balls compared to GO. Graphical abstract: